Mutación en el gen EDA1, Ala349Thr en paciente con displasia ectodérmica hipohidrótica ligada a X - Salas Alanís, Julio César; Cepeda Valdés, Rodrigo; González Santos, Adriana; Amaya Guerra, Mario; Kurban, Mazen; Christiano, Angela M (2011)
Hypohidrotic ectodermal dysplasia (HED) is a very rare disease characterized by the absence of eccrine glands, dry skin, scanty hair, and dental abnormalities. It is caused by mutations within the ED1 gene, which encodes a protein, ectodysplasin-A (EDA). Clinical characteristic are frontal bossing, saddle nose, pointed chin, a prominent supraorbital ridge with periorbital hyperpigmentation, and anodontia. Those affected show great intolerance to heat. We report the fi rst Mexican 2-year-old boy with an Ala349Thr missense mutation from Tamaulipas, México. (Rev Med Chile 2011; 139: 1601-1604).